Enhancing efficiency of grease traps through the addition of lipase producing bacteria for wastewater management in the fresh markets - Kotlakome, Ratchawut; Suttipanta, Nitima; Thongplew, Natapol (Science Essence Journal, 2020)
การเพิ่มประสิทธิภาพของถังดักไขมันด้วยเทคโนโลยีชีวภาพสำหรับการจัดการน้ำเสียในตลาดสด บทคัดย่อ: ตลาดสดทำหน้าที่สำคัญหลายประการสำหรับประชากรในพื้นที่ต่าง ๆ แต่ทว่ากิจกรรมต่าง ๆ ในตลาดสดทำให้เกิดน้ำเสีย (Wastewater) ซึ่งเป็นประเด็นปัญหาสิ่งแวดล้อมที่สำคัญของจังหวัดอุบลราชธานี การวิจัยนี้ทำการศึกษาเทคโนโลยีชีวภาพที่เหมาะสมสำหรับนำมาใช้ในการจัดการน้ำเสียจากตลาดสดเพื่อยกระดับการจัดการของน้ำเสียในตลาดสดเทศบาล 3 และตลาดดอนกลาง จังหวดอุบลราชธานี ผลการศึกษาแสดงให้เห็นว่า Bacillus pumilus. strain UBU5 ที่ผ่านการคัดเลือกแบคทีเรียและทดสอบประสิทธิภาพการกำจัดไขมันในน้ำเสียสังเคราะห์สามารถกำจัดน้ำมันและไขมัน (Oil and grease) ในน้ำเสียและเพิ่มประสิทธิภาพการบำบัดน้ำเสียของถังดักไขมันของครัวเรือนและร้านอาหารได้ นอกจากนี้ผลการศึกษายังแสดงให้เห็นอีกว่าการเติม Bacillus pumilus. strain UBU5 ในถังดักไขมันช่วยลดความถี่ในการตักไขมันออกจากถังดักไขมันโดยที่ยังทำให้ประสิทธิภาพในการบำบัดน้ำเสียไม่ลดลง การศึกษานี้แสดงให้เห็นว่า การเติม Bacillus pumilus. strain UBU5 ในถังดักไขมันมีแนวโน้มที่จะสามารถนำมาใช้ในการยกระดับการจัดการน้ำเสียของตลาดสดได้ Abstract: Fresh markets or wet markets have many functions for local people in many areas. Wastewater is generated from many activities in the market, causing environmental concerns and problems for Ubon Ratchathani, Thailand. This research aims to identify and testy suitable biological technologies for enhancing the levels of wastewater treatment of the Municipal Fresh Market 3 and Don Klang Market in Ubon Ratchathani. The empirical results from the laboratory and pilot testing revealed that adding the identified bacterium - Bacillus pumilus. strain UBU5 – in grease traps of households and restaurants was able to enhance the wastewater treatment efficiency and to reduce oil and grease. In addition, Bacillus pumilus. strain UBU5 was able to minimize the cleaning frequency of the grease traps without compromising the treatment efficiency. In sum, this study demonstrated that Bacillus pumilus. strain UBU5 has a high potential to be used in grease traps in fresh markets for enhancing the wastewater treatment efficiency and reducing the cleaning frequency.